Pelatihan Media Literasi Digital Bagi Pengelola “Buruan Sae” Di Kelurahan Palasari Bandung - Zubair, Feliza (PT. RANESS MEDIA RANCAGE, 2023)
Buruan SAE (Healthy, Natural, Economical) is an integrated urban farming program initiated by the food and agriculture office (DISPANGTAN) of Bandung City. The SAE Hunt Program itself aims to overcome and improve food problems in the city of Bandung, by utilizing existing yards or yards by gardening to meet their respective food needs. Palasari Village, Cibiru District, Bandung City is one of the villages that has succeeded in developing the Buruan Sae program, but in its implementation, the managers feel that there is still a lack of accurate information they have obtained regarding the management of Buruan Sae, especially from social media. Seeing this reality, the PPM KKNM Unpad 2023 team held a seminar on